PENGARUH MOTIVASI, PENGALAMAN KERJA, DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PERUSAHAAN DAERAH AIR MINUM KOTA BALIKPAPAN - Dwi Kusumaningtyas; Tamzil Yusuf; Imam Arywibowo (Fakultas Ekonomi Universitas Balikpapan, 2022)
The purpose of this study was to determine the effect of motivation, work experience and work discipline on the performance of employees of the Regional Water Company in Balikpapan City. The study population was 367 respondents. Using a random sampling technique so that the sample used is 78 respondents. Data collection techniques are observation, interviews and questionnaires. The data analysis method used is multiple linear regression. The results showed that the three variables simultaneously influence the Employee Performance of Regional Drinking Water Companies in Balikpapan City with Discipline partially significantly and dominantly affecting the Employee Performance of Regional Water Companies in Balikpapan City.